Geriatric nutrition - Morley, John E.; Thomas, D.R. (David R.) (Nutrition and disease prevention, 2007)
Offering an overview on nutrition in older persons, this book addresses nutritional requirements, techniques for the clinical assessment of nutrition in older adults, and the management of under nutrition in nursing homes and assisted living environments.